Effects of Whole-Body Electromyostimulation on the Energy-Restriction-Induced Reduction of Muscle Mass During Intended Weight Loss - Willert, Sebastian; Weissenfels, Anja; Kohl, Matthias; von Stengel, Simon; Fröhlich, Michael; Kleinöder, Heinz; Schöne, Daniel; Teschler, Marc; Kemmler, Wolfgang (Frontiers in Physiology, 2019)
Purpose: Overweight and obesity are an increasing problem worldwide. However, most studies that focus on weight reduction by energy restriction and/or aerobic exercise reported considerable loss of muscle mass as well. Increased protein intake and/or resistance exercise might inhibit this detrimental effect during a negative energy balance. Whole-Body Electromyostimulation (WB-EMS), a time effective, joint-friendly and highly customizable training technology, showed similar hypertrophic effects compared with high-intensity resistance training. The aim of this study is to evaluate the effect of WB-EMS on body composition during negative energy balance with maintained/increased protein intake in overweight premenopausal women. Patients and methods: Ninety premenopausal, 25-50 year-old, overweight women were randomly assigned to three groups (n=30 each). (a) Negative energy balance (-500 kcal/d) by energy restriction with compensatory protein intake (CG). (b) Negative energy balance (-500 kcal/d) by energy restriction (-250 kcal/d) and increased physical activity (-250 kcal/d) with increased protein intake (PA). (c) Negative energy balance (-500 kcal/d) due to energy restriction and increased physical activity with increased protein intake plus Whole-Body Electromyostimulation (WB-EMS). The duration of the intervention was 16 weeks. Participants underwent restrictions in kcal per days and supplementation of protein (CG: 1.2 or PA/WB-EMS: 1.7 g/kg body-mass/d) where needed. Bipolar WB-EMS was applied 1.5x week for 20 minutes (85 Hz; 350 µs; intermittent 6 sec impulse, 4 sec rest; rectangular). The primary study endpoint “lean body mass” (LBM) and secondary endpoint body fat mass (BFM) were assessed by bio-impedance analysis (BIA). Results: LBM decreased in the CG and PA group (CG: -113±1872 g; PA: -391±1832 g), but in-creased in the WB-EMS group (387±1769 g). However, changes were not significant (p>.05). Com-paring the groups by ANOVA, no significant differences were observed (p=.070). However, pairwise adjusted comparisons determined significant differences between WB-EMS and PA (p=.049). BFM decreased significantly (p<.001) in all groups (CG: -2174±4331 g; PA: -3743±4237 g; WB-EMS: -3278±4023 g) without any significant difference between the groups (ANOVA: p=.131). Conclusion: WB-EMS is an efficient, joint-friendly and highly customizable training technology for maintaining muscle mass during energy restriction and can thus be considered as an alternative to more demanding resistance exercise protocols.